Petrogenesis for the Chiang Dao Permian high-iron basalt and its implication on the Paleotethyan Ocean in NW Thailand - Yuzhi Zhang (2018)
© 2016, China University of Geosciences and Springer-Verlag Berlin Heidelberg. The Changning-Menglian suture in SW Yunnan has been accepted as the Paleotethyan main ocean. However, it has been a matter of debate as to its southerly extension in NW Thailand (the Chiang Mai-Chiang Rai vs. Nan-Uttaradit zone). Our field investigation identified the high-iron basaltic rocks in the Chiang Dao Permian standard profile in NW Thailand. The high-iron rocks provide crucial records for understanding the controversy on the location of Paleotethyan main ocean in NW Thailand. The Early Permian high-iron samples show extremely high FeOt (20.96 wt.%–25.56 wt.%) and TiO2(6.07 wt.%–6.34 wt.%) and low SiO2(38.54 wt.%–43.46 wt.%) and MgO (1.61 wt.%–2.40 wt.%) contents. Such characteristics are similar to those of the Fenner differentiation trend rarely observed in the natural system, distinct from those of the “normal” Bowen trend. Their chondritenormalized REE and primitive mantle-normalized patterns are generally similar to those of typical OIB. The initial87Sr/86Sr ratios and εNd(t) values range from 0.704 677 to 0.705 103 and 3.16 to 3.48, respectively, falling near the field of typical OIB (oceanic-island basalt). These data synthetically suggest that the Chiang Dao high-iron rocks are the products of high-degree partial melting of peridotite with Fe-rich eclogitic blobs/streaks in response to a seamount setting. In comparison with the Permian tectonic setting in SW Yunnan and NW Thailand, it is inferred that the Paleotethyan Ocean was located between the Shan-Thai terrane of Sibumasu and Sukhothai arc along the Inthanon zone of the Chiang Mai-Chiang Rai rather than Nan-Uttaradit zones.